Trends in the Brazilian scientific production about auriculotherapy (Research, Society and Development, 2020)
This study intends to analyze the trends of Brazilian productions, based on theses and dissertations, about auriculotherapy. It is a narrative review, developed with theses and dissertations available in the Directory of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel. The search took place in January 2020, with the strategy “auriculotherapy” OR “auricular acupuncture”. After applying the selection criteria, 28 studies constituted the corpus of this review. Studies from dissertations (67.9%), concentration area in Nursing (53.6%), with quantitative designs (96.4%) and produced in institutions from southeastern Brazil (75.0%) were predominant. It has highlighted benefits from the practice of auriculotherapy regarding the physical, emotional and neurological health promotion, fighting chronic diseases, besides habits and health improvements. It is concluded that the trends of the Brazilian scientific productions demonstrate the use of auriculotherapy in different aspects, contributing to the promotion and recovery of the health of individuals.